Molecularly-targeted therapy for the oral cancer stem cells. Issue 2 (May 2018) - Ohnishi, Yuichi; Yasui, Hiroki; Nozaki, Masami; Nakajima, Masahiro
Summary: Human cancer tissues are heterogeneous in nature and become differentiated during expansion of cancer stem cells (CSCs). CSCs initiate tumorigenesis, and are involved in tumor recurrence and metastasis. Furthermore, data show that CSCs are highly resistant to anticancer drugs. Cetuximab, a specific anti-epidermal growth factor receptor (EGFR) monoclonal antibody, is used in cancer treatment. Although development of resistance to cetuximab is well recognized, the underlying mechanisms remain unclear. Lapatinib, a dual inhibitor of epidermal growth factor receptor (EGFR)/ErbB2, has antiproliferative effects and is used to treat patients with ErbB2-positive metastatic breast cancer. In this review, cetuximab and lapatinib-resistant oral squamous cell carcinoma (OSCC) cells proliferation and migration signal transduction passway is discussed by introducing our research.